Exacerbating, alleviating, or overcoming? Exploring the nexus between artificial intelligence and the crisis of democracy - Francesco Nasi (Discover Artificial Intelligence)
Abstract When discussing the impact of AI on democracy, the debate predominantly centers on its potential threats, such as misinformation and polarization. However, the role of AI in addressing the democratic crisis is more nuanced. This paper examines three ways that AI might impact the crisis of democracy and discusses the conditions for which these scenarios are more likely to materialize. Firstly, AI could exacerbate this crisis by degrading the public sphere, exacerbating authoritarian rule and increasing power asymmetries. Second, AI could alleviate some aspects of the crisis of democracy by improving public services, rationalizing public debate, or paving the way for new forms of collective participation. Thirdly, AI could overcome this crisis by paving the way for new forms of government beyond the current representative systems. If AI will exacerbate, alleviate, or overcome the crisis of democracy will depend not just on AI itself, but rather on the complex sociotechnical relationship between technology and the cultural, social, economic, legal, and political context in which it is developed. Therefore, we should avoid an essentialist perspective that consider “democracy” and “AI” as givens and embrace a more sociotechnical perspective that looks at how these two elements mutually influence each other.